Perceptions of Technology Integration in Language Acquisition Among English Language Majors - Sijono Sijono; Tuti Tuti; Henry Elisa (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This research examines how English major students perceive the role of technology in their language learning. The study aims to investigate students’ opinions, the technological tools they commonly utilize, the benefits and challenges they perceive, and to provide recommendations for enhancing the integration of technology in English education. Utilizing a quantitative descriptive method, data were gathered through a structured questionnaire containing closed-ended using linkert scale and open-ended questions. The participants comprised students from the English Language Education program at STKIP Persada Khatulistiwa Sintang, specifically those enrolled from semesters 2 to 8 who have experience using technology for learning English. The findings reveal that students regularly use a variety of digital tools, such as mobile applications, to aid their English learning. Participants express favorable views on technology, emphasizing its role in improving vocabulary, grammar, writing, and listening skills. Moreover, technology is perceived as a motivator that enhances engagement, boosts self-confidence, and promotes autonomy in the learning experience. Nevertheless, obstacles persist, such as technical issues, digital distractions, and insufficient structured guidance from educators. The study emphasizes the necessity of institutional support, which includes technical assistance, teacher training, and efficient strategies to reduce distractions. It advocates for a blended learning approach that integrates technology with conventional face-to-face methods to foster a more adaptable and effective educational environment.